Penggunaan Kompos dan Metabolit Sekunder Trichoderma harzianum Terhadap Pertumbuhan dan Hasil Serta Intensitas Penyakit Hawar Daun Pada Tanaman Sawi - Ramli, Sitra; Kalay, A. Marthin; Walsen, Anthony (Jurnal Agroekoteknologi, 2024)
The cultivation of mustard greens (Brassica juncae L.) often experiences problems with low soil fertility and disease attacks. The preventative solution is to utilize natural materials which are waste and secondary metabolites from microorganisms. This research aims to obtain a type of compost and an effective method of application of secondary metabolites of T. harzianum to increase growth and yield and reduce the intensity of leaf blight disease in mustard plants. The treatments tried were compost types, namely sago palm compost, eucalyptus leaf compost, chicken livestock compost, and the secondary metabolite of T. harzianum, which was applied by pouring and spraying. The research used a Split Plot Design with three replications. Data analysis using Minitab 18 software. Effect interaction between the application of secondary metabolites using the spaying method and the type of compost on the growth and yield of mustard greens, as well as leaf blight disease, but each had an independent effect.  The application of secondary metabolites of T. harzianum by using the spray method is equally good in increasing the number of leaves, fresh root weight, and harvest index, while to control leaf blight, the spray method is better. It can reduce the severity of the disease by 35.34%, while the application method is only able to reduce the severity of the disease by 35.34%. disease severity was 18.25%. The eucalyptus leaf compost and chicken livestock compost treatments were equally good in increasing the number of leaves, leaf area, plant height, fresh weight of the shoot, and fresh weight of the roots.  Each type of compost can increase 18.73% and 25.89% leaf area, 12.36% and 12.36% plant height, 20.80% and 24.03% fresh shoot weight, and 11.77% and 13.12% fresh weight of roots.Keywords: biocontrol, compost, secondary metabolites, Trichoderma harzianum.